1994
DOI: 10.1520/jfs13725j
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Ethnicity from Human Mitochondrial DNA Types Determined by Hybridization with Sequence-Specific Oligonucleotides

Abstract: A logistic regression model was developed to predict ethnic group from mitochondrial DNA (mtDNA) types determined by hybridization with sequence-specific oligonucleotide (SSO) probes of the two hypervariable segments of the mtDNA control region. The model was developed with, and tested against, a previously reported data set of 525 individuals from five ethnic groups (African-American, Southeast Asian, Caucasian, Japanese, and Mexican) involving 23 probes at nine regions within the two hypervariable segments [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In fact, studies found that mitochondrial DNA can be used to infer the probable assignment of coarse ethnicity with almost 90% accuracy [ 46 ]. This level of accuracy in predicting investigator-assigned ethnicity could be very useful in forensic investigations [ 47 ]. X chromosome (X-DNA testing) markers: an X chromosome DNA test looks at markers on X chromosome(s).…”
Section: Genetic Markers Used To Infer Ancestry: Autosomal Snps Y-snmentioning
confidence: 99%
“…In fact, studies found that mitochondrial DNA can be used to infer the probable assignment of coarse ethnicity with almost 90% accuracy [ 46 ]. This level of accuracy in predicting investigator-assigned ethnicity could be very useful in forensic investigations [ 47 ]. X chromosome (X-DNA testing) markers: an X chromosome DNA test looks at markers on X chromosome(s).…”
Section: Genetic Markers Used To Infer Ancestry: Autosomal Snps Y-snmentioning
confidence: 99%
“…As mentioned previously, logistic regression may be used when there are only two groups (Connor & Stoneking, 1994). We have constructed a procedure based on logistic regression which resembles the PCA‐QDA approach.…”
Section: Resultsmentioning
confidence: 99%
“…Of the mentioned papers, Connor & Stoneking (1994) and Röhl et al (2001) are the only ones to use data similar to ours. As far as methods go, the approach we propose combines tools from multivariate statistics in a way that differs from those in the above‐mentioned publications.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations